Physio-biochemical evaluation of soybean (Glycine max L.) genotypes exhibiting variable seed coat colour: PHYSIO-BIOCHEMICAL EVALUATION OF SOYBEAN GENOTYPES WITH VARIABLE SEED COAT COLOUR - M T THOMBRE; S V DAMAME; P K LOKHANDE; R M NAIK (Journal of Oilseeds Research, 2017)
Eighteen promising soybean genotypes having different seed coat colour i.e. yellow, green, brown and black were examined for physio-biochemical differences. The highest mean crude protein content was recorded in brown (42.86%), followed by yellow coloured seeds. The yellow coloured seeds recorded the highest mean crude fat content (19.86%). The mean crude fibre content was highest in brown seeds (6.36%), followed by black coloured seeds. Mean seed coat lignin (16.60%), trypsin inhibitor (62.81 TIU g-1) in defatted flour and seed coat peroxidase activity (530 hmoles H2O2 decomposed mg-1 protein min-1) was highest in black coloured seeds. The lowest mean per cent mechanical damage was recorded in black coloured genotypes by ferric chloride test and in brown coloured genotypes by sodium hypochlorite test. The highest seed coat proportion, mean mechanical strength and the lowest mean EC was recorded in black coloured seeds. Mean per cent germination, seed vigour index-I as well as seed vigour index-II and hundred seed weight were recorded highest in yellow seed coat coloured soybean genotypes.